Curating the future museums, communities and climate change - Newell, Jennifer 1971-; Robin, Libby 1956-; Wehner, Kirsten (Routledge environmental humanities, 2017)
"The museum sector has a moral obligation to use its collections and exhibitions and other events to explore some of the inequalities wrought by global warming. The book tackles the broad global issue of climate change through specific collections and in local places. It reflects the Pacific community at its core, but also embraces many other communities who will experience the adverse effects of climate change sooner or later. The book is rich with practical museum experience and detail, as well as critical, analytical and philosophical about where a museum can intervene to speak to this great conundrum of our times"...Provided by publisher